Analysis of the Typical Meteorological Year of Cyprus and Typical House Load - Florides, Georgios A.; Kalogirou, Soteris A.; Theophilou, Kyriacos; Evangelou, Evangelos G. (My University, 2003)
The objective of this paper is to present an analysis of the weather data contained in a Typical Meteorological Year (TMY) and observe the effect of these data on the simulated load of a typical building. The weather data, contained in the TMY, are analysed with respect to the global and diffuse radiation falling on surfaces facing the four orientations, ambient temperature, wind speed and direction, and humidity ratio. Collective results for the whole year indicate that the east wall receives 30% more total radiation than the south wall and the west wall receives only 20% of the beam radiation of the east wall. Three different construction types of a typical house layout are also used in this study and simulated with respect to the heating and cooling loads for a complete year. For the weather encountered in Cyprus the maximum cooling load occurs in July and the maximum heating load in January. The monthly saving in loads by using insulation is of the order of 50% for cooling and 75% for heating.
Keywords: Weather data; Cooling load